HUBUNGAN KETERATURAN POLA MAKAN DENGAN KEJADIAN GASTRITIS PADA MAHASISWA FARMASI STIKes RANAH MINANG - Rina; Anne Rufaridah; Rikaoctriantiaskar; Fonny Kurnia Putri (Rena Cipta Mandiri, 2025)
Gastritis is a chronic inflammation of the stomach lining that causes epigastric pain, anemia, tenderness, and loss of appetite. In West Sumatra, gastritis was the fourth most common disease after acute respiratory infections in 2022 and 2023. A key cause of gastritis is irregular eating patterns, often due to improper diets, spicy foods, or foods containing microorganisms, which increase stomach sensitivity and risk of mucosal bleeding. This study aimed to examine the relationship between eating pattern regularity and the incidence of gastritis among third-year Diploma III Pharmacy students at STIKes Ranah Minang in 2024. A cross-sectional design was used, with primary data collected via questionnaires. The sample consisted of 55 students selected using purposive sampling. Data were analyzed using the Chi-Square test. Results showed that 76.4% had irregular eating patterns and 70.9% experienced gastritis. Among 42 students with irregular eating habits, 88.1% had gastritis, compared to only 15.4% of those with regular patterns. The p-value was 0.000, indicating a significant relationship. Conclusion: There is a relationship between eating pattern regularity and gastritis incidence.